Capsaicin attenuates spermatogenic cell death induced by scrotal hyperthermia through its antioxidative and anti‐apoptotic activities. (12th July 2016) - Park, S. G.; Yon, J.‐M.; Lin, C.; Gwon, L. W.; Lee, J.‐G.; Baek, I.‐J.; Lee, B. J.; Yun, Y. W.; Nam, S.‐Y.
Summary: This study was performed to examine whether capsaicin, the main pungent ingredient of red peppers, exerts protective effects against testicular injuries induced by transient scrotal hyperthermia. Capsaicin (0.33 mg kg −1 ) was administered subcutaneously to mice one hour before heat stress (HS) in a 43°C water bath for 20 min. After 7 days, mice exposed to HS showed low testicular weight, severe vacuolisation of seminiferous tubules followed by loss of spermatogenic cells, and appearance of multinucleated giant cells and remarkable TUNEL‐positive apoptotic cells, as well as weak immunoreactivity of phospholipid hydroperoxide glutathione peroxidase (PHGPx) in spermatogenic cells. Levels of lipid peroxidation and heat shock 70‐kDa protein 1 (Hsp72) and BCL2‐associated X protein (Bax) mRNA were greatly increased, but PHGPx, manganese superoxide dismutase (MnSOD), and B‐cell lymphoma‐extra large (Bcl‐xL) mRNAs were significantly diminished in the testes by HS. However, capsaicin pre‐treatment significantly suppressed the spermatogenic cell death, oxidative stress (levels of MDA, PHGPx immunoreactivity, and Hsp72, PHGPx, and MnSOD mRNA) and apoptosis (levels of TUNEL‐positive cells, and Bcl‐xL and Bax mRNA) in testes by HS. These suggest that capsaicin has a protective effect against spermatogenic cell death induced by scrotal hyperthermia through its antioxidative and anti‐apoptotic activities.